2001
DOI: 10.1097/00005373-200112000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Tractotomy versus Lung Resection: Viable Options in Penetrating Lung Injury

Abstract: Lung resection for penetrating injuries can be done safely with morbidity and mortality rates lower than previously reported. Patient outcome is related to severity of injury rather than type of resection. Tractotomy is associated with a higher incidence of infectious complications and is not associated with shortened operative times or survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 12 publications
0
15
0
4
Order By: Relevance
“…1,3,13 El mecanismo de trauma más frecuente encontrado en este estudio es por arma cortopunzante lo cual se relaciona con lo publicado en la literatura 2 sin embargo, hay estudios en los cuales también se reporta que las heridas por proyectil de arma de fuego podrían llegar a ser más frecuentes 3 esto posiblemente se deba a la facilidad para la adquisición de armas en determinados países y las características de la violencia propia de cada territorio. Cuando se realiza la clasificación de la severidad mediante escalas para identificar la severidad del trauma, se ha descrito que los pacientes que presentan peor pronóstico durante el curso clínico de manejo de su patología traumática son aquellos que tienen un ISS elevado en el momento del ingreso 11 en nuestro estudio se encontró una media de ISS de 16,4 ± 2,91 en el grupo de pacientes que presentaron complicaciones posterior al manejo quirúrgico de su patología traumática. Mario Gasparri et al 11 describe que en su estudio evidenciaron mejor sobrevivencia con valores menores a 16, lo cual permitiría concluir que el promedio de nuestro grupo de pacientes tuvo heridas de una severidad considerable lo cual los predispone a tener un peor pronóstico a largo plazo.…”
Section: Discussionunclassified
“…1,3,13 El mecanismo de trauma más frecuente encontrado en este estudio es por arma cortopunzante lo cual se relaciona con lo publicado en la literatura 2 sin embargo, hay estudios en los cuales también se reporta que las heridas por proyectil de arma de fuego podrían llegar a ser más frecuentes 3 esto posiblemente se deba a la facilidad para la adquisición de armas en determinados países y las características de la violencia propia de cada territorio. Cuando se realiza la clasificación de la severidad mediante escalas para identificar la severidad del trauma, se ha descrito que los pacientes que presentan peor pronóstico durante el curso clínico de manejo de su patología traumática son aquellos que tienen un ISS elevado en el momento del ingreso 11 en nuestro estudio se encontró una media de ISS de 16,4 ± 2,91 en el grupo de pacientes que presentaron complicaciones posterior al manejo quirúrgico de su patología traumática. Mario Gasparri et al 11 describe que en su estudio evidenciaron mejor sobrevivencia con valores menores a 16, lo cual permitiría concluir que el promedio de nuestro grupo de pacientes tuvo heridas de una severidad considerable lo cual los predispone a tener un peor pronóstico a largo plazo.…”
Section: Discussionunclassified
“…In patients with massive hemothorax for blunt chest trauma, the surgical hemostasis must to be achieved quickly: pneumonorrhaphies and wedge resections are preferred but if more conservative interventions do not control hemorrhage, anatomical lobectomy must be performed without delay (6,8). The duration of surgery seems to influence the outcome of patients with lung injuries (16). In a series the mean operative time of conservative treatments (tractotomy) was 2.3 hours, while the mean operative time of anatomic resections (lobectomies and pneumonectomies) was 4.7 hours (7): the disparity of mortality between conservative and non-conservative lung resections for traumatic lesions may be related to the difference in the length of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, patients who required a lobectomy for bronchial injury have a better outcome than patients requiring lobectomy for hemorrhage [24]. More recently, Gasparri et al in a series of 70 thoracotomies for pulmonary hemorrhage reported similar mortality but a much higher rate of pulmonary complications (empyemas, air leaks, and recurrent hemorrhage) following tractotomy compared to pulmonary resection [12]. While the numbers reported are small, these data demonstrate that resectional therapy can be accomplished with a low mortality.…”
Section: Operative Approachmentioning
confidence: 99%